Erratum to: Higher-order relativistic corrections to gluon fragmentation into spin-triplet S-wave quarkonium - Geoffrey T. Bodwin; U-Rae Kim; Jungil Lee (Journal of High Energy Physics, 2023)
A correction to this paper has been published: https://doi.org/10.1007/JHEP11(2012)020